From Olson to Veblen: The Stagflationary Rise of Distributional Coalitions - Jonathan Nitzan (The Bichler and Nitzan Archives, 1992)
This essay deals with the relationship between stagflation and the process of restructuring. The literature dealing with the interaction of stagnation and inflation is invariably based on some explicit or implicit assumptions about economic structure, but there are very few writings which concentrate specifically on the link between the macroeconomic phenomenon of stagflation and the process of structural change. Of the few who dealt with this issue, we have chosen to focus mainly on two important contributors – Mancur Olson and Thorstein Veblen. The first based his theory on neoclassical principles, attempting to demonstrate their universality across time and place. The second was influenced by the historical school and concentrated specifically on the institutional features of modern capitalism. Despite the fundamental differences in their respective frameworks, both writers arrive at a similar conclusion, namely, that the phenomenon of stagflation is inherent in the dynamic evolution of collective economic action, particularly in the rise and consolidation of 'distributional coalitions.'
Keywords: 330; absentee ownership; intangible assets; big business; bonds; capital accumulation; capitalism; collective action; collusion; corporation; credit; degree of monopoly; distributional coalitions; excess capacity; finance; immaterial wealth; income distribution; industry; inflation; institutions; interest; labour liabilities; machine process; material wealth; neoclassical economics; normal rate of return; power; price; profit; productivity; property; sabotage; scarcity; stagnation; stagflation; stocks; tangible assets; technology; United States; value